(untitled) (Research, Society and Development, 2020)
The evolution of studies related to the sustainability of cities has provided a paradigm shift in relation to the control of urban drainage. Solutions based purely on the hygienist concept, of fast water drainage through hydraulic works, have been losing ground to alternatives, which combine non-structural measures with containment at the source of rainwater, the so-called compensatory techniques in urban drainage. In this article, we present reflections about the impact of the increase in impervious areas in cities and on types of compensatory measures, which can be used to control urban drainage. For this, a bibliographic research was carried out, addressing aspects related to soil waterproofing, control of runoff, compensatory measures for the control of urban drainage and analysis of the application of compensatory alternatives for urban drainage in Brazilian cities. A case study was also carried out, focusing on neighborhoods in the city of Teresina, Piauí, with high population density and a high level of urbanization, in which the impermeable areas were estimated, and their increase, between the years 2000 and 2007, using if ArcGIS software. In the studied region it was verified the increase of 26.11% of waterproofed area. As the most viable solutions for use in urban drainage, measures have been identified that use small areas for the retention of rainwater, in individual lots or in public areas, such as lot reservoirs and permeable pavement.